Windows of Opportunity for Lifestyle Interventions to Prevent Gestational Diabetes Mellitus - Phelan, Suzanne (American Journal of Perinatology, 2016)
Gestational diabetes mellitus (GDM) is linked with several acute maternal health risks and long-term development of type 2 diabetes, metabolic syndrome, and cardiovascular disease. Intrauterine exposure to GDM similarly increases offspring risk of early-life health complications and later disease. GDM recurrence is common, affecting 40 to 73% of women, and augments associated maternal/fetal/child health risks. Modifiable and independent risk factors for GDM include maternal excessive gestational weight gain and prepregnancy overweight and obesity. Lifestyle interventions that target diet, activity, and behavioral strategies can effectively modify body weight. Randomized clinical trials testing the effects of lifestyle interventions during pregnancy to reduce excessive gestational weight gain have generally shown mixed effects on reducing GDM incidence. Trials testing the effects of postpartum lifestyle interventions among women with a history of GDM have shown reduced incidence of diabetes and improved cardiovascular disease risk factors. However, the long-term effects of interpregnancy or prepregnancy lifestyle interventions on subsequent GDM remain unknown. Future adequately powered and well-controlled clinical trials are needed to determine the effects of lifestyle interventions to prevent GDM and identify pathways to effectively reach reproductive-aged women across all levels of society, before, during, and after pregnancy.
Keywords: lifestyle intervention; gestational diabetes mellitus; postpartum; preconception; inter-pregnancy